The Effect of African Leaf Tea on Changes in Hematocrit and Blood Pressure - Yayan Hartika; Sri Sumarni; Irmawati Irmawati (Indonesian Journal of Global Health Research, 2024)
Hypertension is a non-communicable disease that often presents without symptoms and is one of the leading causes of death worldwide. The prevalence of hypertension is significantly higher in women compared to men. Among women of childbearing age, hypertension increases the risk of complications during pregnancy, such as preeclampsia and bleeding. Elevated hematocrit levels are strongly associated with hypertension in women, contributing to increased vascular resistance and blood pressure. Efforts to manage hypertension include pharmacological and non-pharmacological therapies. In North Maluku, one of the traditional healing practices passed down through generations for lowering blood pressure involves the use of African leaves (Vernonia amygdalina). This study aims to analyze changes in hematocrit levels and blood pressure in women of childbearing age with hypertension before and after consuming 2.4 grams of African leaf tea (Vernonia amygdalina) for 14 days as a companion to antihypertensive medicine. This research employed a true experimental design with a pretest-posttest control group format. The population consisted of 97 hypertensive women of childbearing age in the service area of the Sanana Public Health Center, Sula Islands, North Maluku. A total of 32 participants were randomly selected. The intervention group received Amlodipine 5 mg as an antihypertensive medication along with 2.4 grams of African leaf tea consumed once daily for 14 days. Blood pressure measurements and venous blood sampling for hematocrit level analysis were conducted on days 8 and 15. Data were analyzed using the General Linear Model Repeated Measures (GLM-RM) approach. The findings demonstrated significant reductions in hematocrit levels and blood pressure among hypertensive women of childbearing age in the intervention group, with a p-value of 0.000. The administration of 2.4 grams of African leaf tea (Vernonia amygdalina) daily for 14 days, as a complementary therapy to antihypertensive medication, is effective in reducing hematocrit levels and blood pressure in women of childbearing age with hypertension.